1991
DOI: 10.1002/dvg.1020120505
|View full text |Cite
|
Sign up to set email alerts
|

Elevated paraquat resistance can be used as a bioassay for longevity in a genetically based long‐lived strain of Drosophila

Abstract: A long-lived (L) strain of Drosophila melanogaster, derived from a normal-lived (R) strain by artificial selection, has a significantly different adult longevity. Previous work has shown that 1) the two strains age in the same manner, 2) the major genes responsible for much of the L strain's extended longevity are located on the 3rd chromosome, and 3) the extended longevity phenotype is significantly modulated by the larval environment. In this report, we investigate the resistance of the L and R strains to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 23 publications
4
60
1
Order By: Relevance
“…), while the L-type animals raised under LD conditions have a survival rate of 5.0 per cent (± 5.0 per cent S.E.M.) (Arking et al, 1991). These differences are statistically significant.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…), while the L-type animals raised under LD conditions have a survival rate of 5.0 per cent (± 5.0 per cent S.E.M.) (Arking et al, 1991). These differences are statistically significant.…”
Section: Methodsmentioning
confidence: 80%
“…Stock construction, measurement of life span, culture conditions, use of the paraquat test to test the presence or absence of the extended-longevity phenotype, and data analysis were carried out as described by Buck et al (1993) and Arking et a!. (1991).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, late-flowering mutants can also be described as extended longevity mutants. Studies with Drosophila have shown that paraquat tolerance can serve as a bio-marker for extended longevity (Arking et al, 1991). This also appears to be the case in Arabidopsis.…”
Section: Discussionmentioning
confidence: 87%